Values in Sports - Grigaitė-Bliūmienė, Kristina (Vilnius University Open Series, 2020)
This paper examines the concept of sports values. Values are universal as they are the axes, supporting all aspects of life. Thus, it can be stated that the participation in sport activities is also based on the axes of values. The research aim: to analyse the concept of values in sports and the experience in the education of values through sports. The research method – the analysis and review of the foreign and Lithuanian scientific literature.